2014
DOI: 10.1159/000365036
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Challenges and Opportunities during the Weaning Period and in Young Childhood

Abstract: The early years of life are a period of very rapid growth and development. In this critical phase, food preferences are formed which carry over into childhood and beyond and foundations are laid for a healthy adult life. Excess energy, imbalances in macronutrient quality, and nutritional deficiencies may form inappropriate nutritional signals, leading to metabolic disturbances and affecting the obesity risk. For instance, the intake of protein and sugar-sweetened beverages in young children has been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 82 publications
0
37
0
Order By: Relevance
“…Recent reviews of European studies showed that mean protein intakes during the first 2 years of life were either close to or above the recommended limits in most studies. 3,19 Daily protein needs were covered for 99% of our population. However, protein consumption above the recommended levels was found for 50% of our infants; this ratio increased over time, which might be a risk factor of obesity later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of European studies showed that mean protein intakes during the first 2 years of life were either close to or above the recommended limits in most studies. 3,19 Daily protein needs were covered for 99% of our population. However, protein consumption above the recommended levels was found for 50% of our infants; this ratio increased over time, which might be a risk factor of obesity later in life.…”
Section: Discussionmentioning
confidence: 99%
“…An n‐6/n‐3 ratio of <10 is recommended by the World Health Organization (WHO) for nutraceuticals to have the potential to reduce neurological, inflammatory, and cardiovascular disorders; in contrast, the European Nutritional Societies recommend an n‐6/n‐3 ratio of 5 (Alles, Eussen, & Van Der Beek, ). Among different species of Sargassum studied for FA profiling, all except S. pallidium (Turner) C. Agardh showed an n‐6/n‐3 ratio <5 (Chen et al., ).…”
Section: Nutritional Characteristics and Bioactivity Of Seaweed Lipidsmentioning
confidence: 99%
“…High intakes of dietary sugar are extensively discussed to have adverse health consequences. Concerns relating to high sugar intakes comprise its contribution to the development of dental caries, excess weight gain, type 2 diabetes and CVD, as well as a lower nutritional adequacy of the diet, as added sugar itself does not provide essential nutrients (1)(2)(3)(4) . Therefore, current dietary guidelines do emphasise the limitation of dietary sugar intake, focusing on the avoidance of sugar added during processing (added sugar) rather than sugars naturally occurring in foods (5) .…”
mentioning
confidence: 99%